Merging a landscape management planning approach with the community capitals framework: Empowering local groups in land management processes in Bocas del Toro, Panama - Gutiérrez Montes, Isabel A. (2009)
Community management of natural resources is well supported by many field experiences as an effective way to improve people’s well-being while maintaining their natural resource base. The approach has been reasonably achieved within community groups and the community as a whole. Nonetheless, there are fewer experiences at multi-community or regional levels (landscape). In this article we describe a participatory action research project that led to a successful multicommunity regional management plan. Using the Community Capitals Framework to help community members see their region as a system with assets and the managed landscape approach to focus on key decision points, the process led to an inclusive and successful planning process with high potential for implementation. We highlight the lessons learned from this experience and identify potential limitations to its use.